Description of Mesophylax isly sp. nov. (Trichoptera, Limnephilidae) from Morocco, and new genus records from the Balkans - Taybi, Abdelkhaleq Fouzi; Mabrouki, Youness; Ibrahimi, Halil (Zootaxa, 2024)
The male and female genitalia of Mesophylax isly Ibrahimi, Taybi & Mabrouki sp. nov. (Limnephilidae) are described based on material collected from the Isly River in Morocco. The new species is most similar to Mesophylax aspersus hoggarensis Malicky 1988 known from Algeria, from which it differs in the formation of intermediate appendages, inferior appendages, parameres, and segment IX in males, as well as in the formation of segment X, lateral shoulders of segment IX, supragenital plate and vulvar scale in females. Information is provided on the autecology and habitat of the new species, as well information about other species co-occurring with M. isly sp. nov. We also report new localities for Mesophylax aspersus aspersus Rambur 1842 from Kosovo and Morocco and the first record of Mesophylax impunctatus aduncus Navás 1923 from Albania.